Hubungan Motivasi Belajar Dan Keaktifan Belajar Dengan Hasil Belajar Siswa SD Gugus III Kecamatan Tanete Riattang Kabupaten Bone - Dian Darlina Sari; Arismunandar Arismunandar; Muhammad Irfan (Departement of Mathematics Education, 2024)
The formulation of the problem in this study is how is the description of learning motivation, learning activity, learning outcomes of Elementary School Cluster III, Tanete Riattang District, Bone Regency? and is there a significant relationship between learning motivation and learning activity with learning outcomes of Elementary School Cluster III, Tanete Riattang District, Bone Regency? This study is a correlation study that aims to determine the description of learning motivation, learning activity, learning outcomes and the relationship between learning motivation and learning activity with learning outcomes of Elementary School Cluster III, Tanete Riattang District, Bone Regency. The research approach is a quantitative approach. Research data were obtained through questionnaires and documentation. The population in the study were all Grade VI students at Elementary School Cluster III, Tanete Riattang District, Bone Regency, totaling 83 students. The sample in the study amounted to 83 students. The data analysis technique was descriptive and inferential statistical analysis. The results obtained in this study are a description of learning motivation showing a very high category and learning activity showing a very high category in the questionnaire results obtained and learning motivation and learning activity have a significant relationship to student learning outcomes, especially in Class VI of Elementary School Gugus III, Tanete Riattang District, Bone Regency.